Pengembangan Destinasi Wisata Edukasi Agrikultur Desa Dengok dengan Media Sosial - Prasetyo Jati, Didit Gunawan (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Dengok Village is one of the villages located in Playen District, Gunungkidul. Most of Dengok Village’s residents work as farmers and planters. However, Dengok Village area is dominated by marginal land which is dry and less fertile. Therefore, Dengok Village’s farmers rely on the rainy season to irrigate agricultural land. This causes farmers to only be able to harvest a maximum of two times a year. To increase their income, farmers plant various types of trees on community forest land. The existence of rainfed rice fields and community forests proves that Dengok Village has great potential in the agricultural sector, but has not been fully utilized. Based on these problems, the authors compiled this dedication paper, with the aim of developing agricultural potential of Dengok Village through the formation of agricultural educational tourism destination and its marketing methods, so as to be able to advance the economic welfare of the local population. The method is carried out online by observing data on the internet. The results of the dedication are activity ideas that can be applied in Dengok Village agricultural education tours and marketing tips through social media, so that it is more easily recognized and attracts more people.